2016
DOI: 10.1097/bpb.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

Humeral lateral condyle fractures in children: redefining the criteria for displacement

Abstract: The aim of this study is to define paediatric lateral humeral condyle fractures prone to later displacement. The authors reviewed 106 children who were treated surgically for this fracture. There were 74 boys and 32 girls with an age range of 3-10 years. The study included 27 minimally displaced and 79 displaced fractures. The average follow-up was 50 months. Binary logistic regression model indicated that 6-8-year-old children with minimally displaced fractures and who underwent immediate surgery have a bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
1
16
3
Order By: Relevance
“…15 In our study, the odds ratio of having conservative management per month increase in age was statistically significant (2.1), which was contrary to a previous study that reported that the need for surgical fixation showed significant association with older age group. 11 In young children, because of the largely cartilaginous nature of capitellum, the lateral condyle is not always well visualized on plain radiographs, and this makes the clinical diagnosis of lateral condylar fractures and assessment of their epiphyseal extension difficult. [4][5][6] This could partly explain the preference of surgical management over conservative management in younger children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In our study, the odds ratio of having conservative management per month increase in age was statistically significant (2.1), which was contrary to a previous study that reported that the need for surgical fixation showed significant association with older age group. 11 In young children, because of the largely cartilaginous nature of capitellum, the lateral condyle is not always well visualized on plain radiographs, and this makes the clinical diagnosis of lateral condylar fractures and assessment of their epiphyseal extension difficult. [4][5][6] This could partly explain the preference of surgical management over conservative management in younger children.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have reported the usage of surgical management even in the minimally displaced fractures and a better chance for satisfactory results subsequently. 11 This points to the fact that there exist wide practice variations in management of lateral condyle elbow fractures in pediatric patients across various centers in the world. Lateral condyle humeral fractures have a risk of displacement because of pull of the extensor muscles on the condyle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review reported that 14.9% (53/355) had secondary fracture displacement during conservative treatment [ 26 ]. Some scholars even proposed that regardless of whether the fracture was displaced or not, all children with HLCFs required surgical treatment [ 27 ]. So far, the diagnosis, clinical classification, and treatment decisions of children with HLCFs have mainly relied on radiographs of the elbow joint.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown improved outcomes with surgical intervention with displacement 2 mm or greater. 9,10 The goal with surgical intervention is an anatomic reduction of the articular surface, with stable internal fixation to prevent fracture displacement and encourage bony union. For minimally displaced fractures, this may be achieved with closed reduction and internal fixation with Kirshner wires (K-wires) or with percutaneous screw fixation.…”
Section: Introductionmentioning
confidence: 99%